Sickness behaviour: Causes and effects - M. Viljoen (South African Family Practice)
This paper discusses sickness behavior as a central motivational state. It deals with the adaptational value and underlying mechanisms of sickness behavior and with the consequences of the body's failure to terminate the activity of the symptoms-producing cytokines .